OVERACTIVE BLADDER (World Science, 2020)
In recent years, there has been a steady increase in patients visiting a specialist for what is known as overactive bladder syndrome. Due to the extremely negative impact of the disease on patients' quality of life, timely diagnosis and adequate treatment choices are of the utmost importance. The guidelines presented include a description of the etiology and pathogenesis, basic principles of diagnosis, and current methods of treatment for this category of patients.